Peningkatan Turnover Intention Yang Dipengaruhi Job Insecurity Melalui Stres Kerja Pada Karyawan Outsourcing PT. Industri Kemasan Semen Gresik (IKSG) - WIDA YANTI, AINUNG; FRIANTO, AGUS (Jurnal Ilmu Manajemen (JIM), 2019)
Abstract The purpose of this research is to test and analyze the effect of job insecurity on turnover intention through job stress on outsourced employees PT. Industri Kemasan Semen Gresik (IKSG). This research is a causality research with a quantitative approach. The sampling technique using samples saturated by the number of 92 respondents at PT Industri Kemasan Semen Gresik (IKSG). The statistical analysis used in this study is Partial Least Square (PLS) with the help of smartPLS 3.0 software. The results of this study explain that job insecurity does not effect turnover intention, job insecurity has a positive and significant effect on job stres, job stres has a positive and significant effect on turnover intention and job insecurity has a positive and significant effect on turnover intention through job stres. Keywords: job insecurity; job stress; turnover intention.